Southern Beauty, Waltz-Song - G. Valisi::::::::: (G. Venturini)
Piano score, 6 p. Score c1904 by Valisi Bros. On cover is birds-eye photo of the exposition, printed in blue. Publishers advertisement on verso of last leaf.